THE IMPACT OF EXTERNAL AUDITING ON THE QUALITY OF PERFORMANCE OF IRAQI BANKS (World Economics and Finance Bulletin, 2023)
The external audit constitutes an important mechanism for maintaining the mutual and necessary trust in the financial relations between the different parties in the Iraqi society, because of the great role it plays in meeting the needs of the parties through a neutral and independent technical opinion regarding the numbers and financial data presented by the founder’s management, as the study aims to highlight Highlighting the history of auditing and external auditing as one of the most important mechanisms that contribute to improving the quality of financial statements and their impact on the quality of performance of Iraqi banks